2009
DOI: 10.1186/1471-2407-9-216
|View full text |Cite
|
Sign up to set email alerts
|

Fatty fish and fish omega-3 fatty acid intakes decrease the breast cancer risk: a case-control study

Abstract: BackgroundAlthough it is believed that fish ω-3 fatty acids may decrease breast cancer risk, epidemiological evidence has been inconclusive. This study examined the association between fish and fish ω-3 fatty acids intake with the risk of breast cancer in a case-control study of Korean women.MethodsWe recruited 358 incident breast cancer patients and 360 controls with no history of malignant neoplasm from the National Cancer Center Hospital between July 2007 and April 2008. The study participants were given a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 51 publications
2
59
0
1
Order By: Relevance
“…Case-control studies generally find an inverse association between dietary intake and/or red blood cell (RBC) fatty acid content of EPA and DHA and breast cancer risk (19)(20)(21). Prospective studies also have generally shown an inverse association between consumption of omega-3 fatty acids from fish and/or fish oil supplements and breast cancer incidence (18).…”
Section: Introductionmentioning
confidence: 99%
“…Case-control studies generally find an inverse association between dietary intake and/or red blood cell (RBC) fatty acid content of EPA and DHA and breast cancer risk (19)(20)(21). Prospective studies also have generally shown an inverse association between consumption of omega-3 fatty acids from fish and/or fish oil supplements and breast cancer incidence (18).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, individuals who consume large amounts of crucian carp have higher risk of breast cancer, may be associated with the contaminated degree of crucian carp by heavy metals . Kim et al (2009) investigated the association between fatty fish and their fatty acids intake and the incidence of breast cancer in Korean women. They found that high consumption of fatty fish is associated with a reduced risk for breast cancer, and that the intake of ω-3 fatty acids from fish is inversely associated with postmenopausal breast cancer risk.…”
Section: 7879 Intakes Of Freshwater Fish and Their Fatty Acids And Tmentioning
confidence: 99%
“…In the past few decades, epidemiological studies (Brennan et al, 2010;Lambrechts et al, 2011;Gao et al, 2013) have suggested that a healthy diet and lifestyle is critical factor for the prevention of breast cancer. Many authors have analysed relationship between the fish intake and the risk of breast cancer, however the results have been inconsistent (Wirfalt et al, 2002;Terry et al, 2003;Hirose et al, 2006;Engeset et al, 2006;Brustad et al, 2007;Kim et al, 2009;Sala-Vila and Calder, 2011;Zheng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Any discrepancies between reviewers were addressed by a joint reevaluation of the original article. We identified 30 potentially relevant articles concerning fish consumption and breast cancer risk (9,38). After duplicated studies were excluded, the remaining publications in the meta-analysis of fish consumption and breast cancer included 27 articles: eight cohort studies and 18 case-control studies.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…However, epidemiological studies assessing the relation between breast cancer and fish consumption are inconclusive. Some studies showed a decrease in risk (9,10), and some found no association (11,12), while others revealed an increased risk associated to high consumption of fish (13,14). We therefore performed a systematic review and meta-analysis to assess the association between fish consumption and breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%